Volcanic soils of the High Börzsöny and their relationship with geomorphological conditions - Madarász, Balázs; Jakab, Gergely (Hungarian Geographical Bulletin, 2009)
Heretofore very little research has been done on a specific soil type in Hungary called „erubáz”, which develops on volcanic rocks. Its largest uniform and unbroken spot is located in the central part of Börzsöny Mountains (High Börzsöny). It is assumed that in reality this spot extends beyond its contours indicated in the soil map of the area. The main objective of the research project was to carry out a detailed analysis of this soil type and to identify its subtypes and varieties. A large scale soil mapping (1:25 000) and geomorphological mapping (1:10 000) was performed in order to determine the spatial distribution of the subtypes and varieties and to investigate the relationship between the territorial extension and geomorphological position. The sampling network was set after a thorough study of environmental conditions (e.g. relief, botanical conditions etc.). 38 soil profiles and 115 boring samples were taken by Pürckhauer auger because of the significant inhomogeneity of the studied area. Our former studies (Madarász, B. 2009) revealed that two varieties of the s-called ‘erubáz’ soil, i.e. the brown and the black erubáz can be distinguished in the study area. Black erubáz soils occur on narrow ridges with high elevations as described in the classical definition by P. Stefanovits. After a few 10 meters from the crest of the ridges downslope they will be replaced by the brown erubáz. The latter can be found on the top of the ridges and on their slopes as well whilst the black erubáz appears only above 700 m a.s.l. except one smaller spot. The occurrence of the brown erubáz is controlled by soil climatic conditions. It develops mainly where enough moisture and heat are available for the decomposition of organic material but they are not sufficient and the geomorphic position is not suitable for the development of forest soils.